Сравнительный анализ способов автономного производства водорода - Трошенькин, В. Б.; Зипунников, Николай Николаевич; Трошенькин, Борис Александрович (НТУ "ХПИ", 2012)
Advantages and disadvantages of process of hydrogen manufacture by electrolyses of waters and by reaction of water with aluminum-silicic alloys are considered. The skilled data on chemical activity of some alloys are resulted. Significant advantages of process of hydrogen reception from water with the help of the alloys received from an inorganic part of coal are shown.
Keywords: водород; производство водорода; силиколевый способ; вода; едкий натр; электролитический метод; газгольдеры; электролизеры; аморфизация